Peran Legalitas Nomor Induk Berusaha (NIB) dalam Mendorong Formalisasi dan Pertumbuhan UMKM di Kelurahan Kalisari Surabaya - Fadilah, Istianatul; Pertiwi, Tri Kartika (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Business Identification Number (NIB) is an important part of the business licensing system because it helps Micro, Small, and Medium Enterprises (MSMEs) to obtain licenses, access funding, and participate in various government programs. In addition, the NIB also serves as a legal identity that forms the basis for MSMEs to start and run their business activities officially. However, in reality, many business actors still do not understand what the NIB is or how to apply for one, causing them to encounter difficulties in the NIB registration process. This condition is clearly evident in Kalisari Village, where many business actors do not have an NIB not because they do not need one, but because of a lack of information and guidance. Through an internship program run under the guidance of the Cooperative Office, MSMEs assistance activities in Kalisari Village focus on providing education, disseminating information on regulations, assisting with the use of the OSS system, and assisting business owners with the registration process.